Personalistic bioethics in supporting marriages in a situation of breakdown - Latre-Campos, Yolanda (2025)
The practice of family support for families in vulnerable situations—primarily family counseling—is directly connected to bioethics and the family, to that biofamily focused on the protection and development of each member while respecting their personal dignity. This article aims to present a very concrete bioethical contribution—based on praxis—within the personalist approach to family support and counseling in problems related to the breakdown of canonical marriages. Not surprisingly, this approach contemplates the total care of the family and each of its members, the freedom and responsibility of actions, as well as the solidarity that encompasses the well-being, not only psychophysical but integral, of the family in crisis. It also aims to continue forging paths in the necessary scientific interdisciplinarity between Bioethics and Family Sciences. From this starting point, the article aims to delve deeper into the care of marriages in crisis from a holistic and multidisciplinary perspective, combining the juridical and pastoral nature of the sacrament of marriage with the psychological and spiritual needs of the spouses and, consequently, of their offspring, if any; and the personalist and humanist ethics that demand to be developed, even more splendidly, in these situations of particular fragility and vulnerability.